The Aftermath of Climate Justice in Lofoten, Norway - Otabe, Jennifer Oka (The University of Bergen, 2023)
The impacts of climate change are a pressing issue for the present and a looming concern for the future. We are witnessing global repercussions of our actions, from intense storms to prolonged drought. Our planet is at risk, necessitating immediate efforts to reduce this risk. This study focused on understanding the implications of climate justice in Lofoten, Norway, a region that has become a focal point for climate justice due to seismic activities for oil exploration. These activities could impact the local biodiversity, tourism, and fishing industries and obstruct the achievement of sustainable development goal 13, which pertains to climate action. The study aimed to achieve the overarching objective of establishing whether a robust basis for sustainable development in the area was realized or not. An online survey was conducted among the local population to gather the necessary data, with 11 individuals participating. Additionally, seven in-depth interviews were conducted. The results indicated that the community favoured the ruling against oil exploration in Lofoten, viewing it as a positive development for the community. Residents of Lofoten have implemented resilience strategies to ensure the long-term well-being of their region, protect its unique ecosystem and resources and reduce the potential adverse effects of oil exploration. These strategies include preserving the natural beauty of their environment, safeguarding their traditional lifestyle, and actively participating in activism and community initiatives. Master's Thesis in Geography GEO350 MASV-GEOG MASV-PHYG MASV-MEHA MPGEOGR